Getting It Done Four Ways to Translate Strategy into Results - Yukl, Gary; Yukl, Gary; Lepsinger, Richard (Center for Creative Leadership, 2007)
A recent survey indicates that many of today's business leaders believe their organizations are not only inadequate at implementing strategy but also unlikely to get better at this critical challenge. Other research on managers has identified four leadership behaviors that are useful in enhancing the execution of business strategy.